1996
DOI: 10.1159/000289062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Psychosocial Correlates of Antenatal Depression: A Review

Abstract: In contrast to the considerable research on postnatal depression, less attention has been paid to that occurring during pregnancy – antenatal depression (AD). However, recent investigations have studied depression among pregnant women not necessarily requiring psychiatric hospitalization but needing psychological support and help. A controlled study showed that the rate of AD was significantly higher than that of depression among non-pregnant women: the reported incidence varies between 4 and 29%. AD was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 49 publications
3
32
1
4
Order By: Relevance
“…The major limitation of our study was that we were not able to examine the risk factors for depression, such as social factors (27), history of depression, lack of partner, or family violence (28,29). The CES-D scale evaluates frequency of depressive symptoms only in the previous week; lack of evaluation and diagnosis by a psychiatrist is also another limitation.…”
Section: Was Bothered By Things That Usuallymentioning
confidence: 97%
“…The major limitation of our study was that we were not able to examine the risk factors for depression, such as social factors (27), history of depression, lack of partner, or family violence (28,29). The CES-D scale evaluates frequency of depressive symptoms only in the previous week; lack of evaluation and diagnosis by a psychiatrist is also another limitation.…”
Section: Was Bothered By Things That Usuallymentioning
confidence: 97%
“…In the epidemiological studies to date, depression has been reported in 4-29% of mothers during pregnancy [16], and in 10-24% of mothers following childbirth [17]. The lifetime prevalence of depression among the entire population in Japan is reported at between 15-20% [18], and it is believed that depression can be considered a relatively commonly manifested disorder not only in pregnancy and the perinatal period, but during the subsequent years of child-rearing.…”
Section: Maternal Depressionmentioning
confidence: 99%
“…The lifetime prevalence of depression among the entire population in Japan is reported at between 15-20% [18], and it is believed that depression can be considered a relatively commonly manifested disorder not only in pregnancy and the perinatal period, but during the subsequent years of child-rearing. There have been reports that maternal depression in the perinatal period affects the child's development [5,16,19], but few have touched on depression in mothers engaging in child care at 1 year postpartum. There is one longitudinal study by Sugawara et al [9], but they have not evaluated incidence in their report.…”
Section: Maternal Depressionmentioning
confidence: 99%
“…These home visits were primarily geared towards groups prone to child abuse, i.e., women with unwanted pregnancies, pregnant adolescents and low-income families [5][6][7]. On the other hand, several studies have been made on the association between unwanted pregnancies and perinatal depression [8][9][10]. In Japan, a home visiting program, Boshi-AiikuKai, has been sponsored by the Mother-Child Nursing Association since the 1930s.…”
Section: Introductionmentioning
confidence: 99%